Effect of Drying Temperatures on Starch-Related Functional and Thermal Properties of Acorn Flours - Correia, P R; Beirão-da-Costa, M L (Journal of Food Science, 2011)
Abstract: The application of starchy flours from different origins in food systems depends greatly on information about the chemical and functional properties of such food materials. Acorns are important forestry resources in the central and southern regions of Portugal. To preserve these fruits and to optimize their use, techniques like drying are needed. The effects of different drying temperatures on starch-related functional properties of acorn flours obtained from dried fruits of Quercus rotundifolia (QR) and Quercus suber (QS) were evaluated. Flours were characterized for amylose and resistant starch (RS) contents, swelling ability, and gelatinization properties. Drying temperature mainly affected amylose content and viscoamylographic properties. Amylograms of flours from fruits dried at 60 °C displayed higher consistency (2102 B.U. and 1560 B.U., respectively, for QR and QS). The transition temperatures and enthalpy were less affected by drying temperature, suggesting few modifications in starch structure during drying. QR flours presented different functional properties to those obtained from QS acorn flours. The effect of drying temperatures were more evident in QR.
Keywords: acorn flours; drying; Functional properties; starch; thermal analysis

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis